2000
DOI: 10.1177/088307380001501001
|View full text |Cite
|
Sign up to set email alerts
|

Topical Review: Hypomelanosis of Ito: Clinical Syndrome or Just Phenotype?

Abstract: The term hypomelanosis of Ito is applied to individuals with skin hypopigmentation along the lines of Blaschko. Even though originally described as a purely cutaneous disease, subsequent reports have included a 33% to 94% association with multiple extracutaneous manifestations mostly of the central nervous and musculoskeletal systems leading to frequent characterization as a neurocutaneous disorder. A number of reports claimed familial occurrence and supported single gene inheritance for hypomelanosis of Ito, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
64
0
9

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 88 publications
2
64
0
9
Order By: Relevance
“…Disorders with pigmentary anomalies along the lines of Blaschko can be associated with abnormal systemic features, particularly of the central nervous, musculoskeletal, and ocular systems [Nehal et al, 1996;Ruggieri and Pavone, 2000]. Nehal et al [1996] analyzed the symptoms and signs of 54 patients with hypopigmentation and hyperpigmentation along the lines of Blaschko.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders with pigmentary anomalies along the lines of Blaschko can be associated with abnormal systemic features, particularly of the central nervous, musculoskeletal, and ocular systems [Nehal et al, 1996;Ruggieri and Pavone, 2000]. Nehal et al [1996] analyzed the symptoms and signs of 54 patients with hypopigmentation and hyperpigmentation along the lines of Blaschko.…”
Section: Discussionmentioning
confidence: 99%
“…HOI is the third most common neurocutaneous disorder, after neurofibromatosis and tuberous sclerosis [4,5]. It is diagnosed in 1 per 8000-10000 unselected patients in general paediatric outpatient clinic and 1 out of every 790 in a paediatric dermatology clinic [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal abnormalities, particularly translocation and mosaicism have been reported in approximately 50% of cases [5]. It is suggested that HOI is not a single condition but a phenotype of chromosomal mosaicism [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HI or incontinentia pigmenti achromians (MIM#300337) represents a heterogeneous group of early-onset sporadic neurocutaneous disorders, resulting from chromosomal mosaicism 1 . Neurological manifestation may include: cognitive impairment, epilepsy, spasticity, cerebellar ataxia and microcephaly 2 .…”
mentioning
confidence: 99%